KAJIAN YURIDIS TINDAK PIDANA PENCUCIAN UANG TERKAIT DENGAN PEMBUKTIAN TERBALIK DALAM PERKARA TINDAK PIDANA KORUPSI DI INDONESIA (Studi Putusan PN Nomor. 1252/Pid.B/2010/PN.Jkt.Sel, jo Putusan PT Nomor. 08/PID/TPK/2011/PT-DKI jo Putusan Kasasi Mahkama - Anton Diary Steward Steward Surbakti (jurnal.unprimdn.ac.id, 2018)
In this research, the writer analyzed and investigated money laundering crime which is related of reverse authentication of Drs. Bahasyiem Assifie, M.Si bin Khalil Sarinoto as convict in District Court South Jakarta, high court Jakarta and Supreme Court sentenced imprisonment money substitute and fine. It declared and be sure guilty did money laundering crime. This research used juridical normative to know the principle application and the rule of law which was effect in this research. The analysis and finding law research was used Analcites Descriptive. The process of this research was collecting data and law facts. It called the data. Reverse authentication which was applicative in this court found many problems in different perception about verification crime.